Analisa Aliran Barang dan Informasi dengan Menggunakan Value Stream Mapping di PT. SIM - Basuki . (JURNAL CITRA WIDYA EDUKASI, 2018)
The purpose of this study is to describe the flow of process, materials and information using value stream mapping, define key performance indicator system, determining the points that could be the focus of improvement and propose improvements to describe the future value stream mapping. The method used in this study is the description which describe and analyze the real conditions to give the proposed improvements in the future. While the results of this study is to determine the Process Cycle Efficiency (PCE) as an indicator of the performance of the current condition value of 0.41% and the conditions proposed by 0.87%. The conclusion that in order to raise the value added ratio on a system can be done by applying the tools pull system.